Approximation of harmonic functions on compact sets in ℂ - Andrievskii, V.V. (Український математичний журнал, 1993)
The direct theorem of the theory of approximation of harmonic functions is established in the case of functions defined on a compact set, the complement of which with respect to ℂ is a John domain.